2012
DOI: 10.1097/igc.0b013e318272f2c9
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Long Noncoding RNAs in Cervical Intraepithelial Neoplasia

Abstract: Through the analysis of L-SAGE libraries constructed from cervical specimens, we provide the first lncRNA expression profile of the cervix and demonstrate aberrant expression in early-stage neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Using a range of techniques, such as microarray, 18 RNA sequencing, 19 and real-time PCR, 20 many studies have confirmed that lncRNA expression levels differ between normal and tumor tissues and vary among tumor types. [21][22][23] Although some of these abnormal expression patterns may be secondary effects from the cancer transformation, several factors suggest that lncRNAs could influence tumorigenesis. These factors include the tremendous complexity and diversity of the lncRNA landscape, the finding that lncRNAs are often located at crucial sites (eg, regions of singlenucleotide polymorphisms (SNPs), amplifications, or at common breakpoints), the presence of sequence motifs and other elements that result in specific structures, their regulation, and their functional relationships with other nucleic acids and proteins.…”
Section: Lncrnas In Cancermentioning
confidence: 99%
“…Using a range of techniques, such as microarray, 18 RNA sequencing, 19 and real-time PCR, 20 many studies have confirmed that lncRNA expression levels differ between normal and tumor tissues and vary among tumor types. [21][22][23] Although some of these abnormal expression patterns may be secondary effects from the cancer transformation, several factors suggest that lncRNAs could influence tumorigenesis. These factors include the tremendous complexity and diversity of the lncRNA landscape, the finding that lncRNAs are often located at crucial sites (eg, regions of singlenucleotide polymorphisms (SNPs), amplifications, or at common breakpoints), the presence of sequence motifs and other elements that result in specific structures, their regulation, and their functional relationships with other nucleic acids and proteins.…”
Section: Lncrnas In Cancermentioning
confidence: 99%
“…It is increasingly understood that lncRNAs are important molecules involved not only in normal development but also in tumorigenesis [7]. In fact, there are emerging evidence showing that lncRNAs are involved in pathological development of cervical cancer [8]. For example, MEG3 (maternally expressed 3) is a lncRNA playing tumor suppressor role in several cancers by inducing cell cycle arrest and apoptosis [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the role of lncRNAs in CC are very preliminary. Until now only one research has detected increased levels of aberrant lncRNA expression in cervical intraepithelial neoplasia (CIN) specimens representing mild, moderate, and severe histopathologic grades, respectively, suggesting that lncRNAs may play important roles in the development and progression of precancerous lesions or carcinomas [10]. However, the overall pathophysiological contributions of lncRNAs in CC remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%